Promoting the Effectiveness of Language Teaching Through Online Academic Word Lists and Extensive Reading in the COVID-19 Pandemic - Kamaşak, Rıfat; Soyaltın, Tuğçe Ezgi (My University, 2021)
Restricted online class times and limitations of online teaching along with the emotional and psychological challenges faced by students require adequate pedagogical implementations in the COVID-19 pandemic. In line with this requirement, while academic word lists can help students to focus on prioritised vocabulary, extensive reading can create a pleasant reading environment which might motivate students in unprecedented conditions. Thus, this study aims to propose some pedagogical suggestions such as academic word lists and extensive reading which might contribute to language learning performance of students in the COVID-19 pandemic.
Keywords: Language Teaching